Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.omtn.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA SNHG1 Promotes Basal Bladder Cancer Invasion via Interaction with PP2A Catalytic Subunit and Induction of Autophagy

Abstract: Although basal muscle-invasive bladder cancers (MIBCs) are predominant, are more aggressive, and have bad prognoses, molecular mechanisms underlying how basal MIBC formation/progression have been barely explored. In the present study, SNHG1, a long non-coding RNA, was shown to be expressed at higher levels in basal MIBC cells than in other types of bladder BC cells, and its presence could promote basal MIBC cell invasion. The results revealed that SNHG1 specifically induced MMP2 expression via increasing its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…34 This phenomenon could be activated or restrained by various types of modifications, such as phosphorylation or glycosylation. 35,36 Xu et al 37 TGF-β1 at the transcriptional level. 28 This phenomenon indicated that SNHG17-recruited c-Jun triggers TGF-β1-induced SNHG17.…”
Section: Discussionmentioning
confidence: 99%
“…34 This phenomenon could be activated or restrained by various types of modifications, such as phosphorylation or glycosylation. 35,36 Xu et al 37 TGF-β1 at the transcriptional level. 28 This phenomenon indicated that SNHG17-recruited c-Jun triggers TGF-β1-induced SNHG17.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, SOX2OT upregulates SOX2 expression by sponging miR-200c 10 . In addition, many lncRNAs such as CASC9 42 , SNHG1 43 , TUG1 44 , and NBAT1 45 are associated with the occurrence and development of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a large number of lncRNAs have been found to play an important role in invasion, metastasis and drug resistance in BC [8][9][10]. For instance, lncRNA-SNHG1 promotes basal MIBC cell invasion by interacting with the PP2A catalytic subunit and inducing autophagy [11]. LncRNA-SLC16A1-AS1 induces metabolic reprogramming as a target and coactivator of E2F1 in BC progression [12].…”
Section: Introductionmentioning
confidence: 99%